2021
DOI: 10.1002/jbt.22853
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptide LTX‐315 reverses the cisplatin chemoresistance of ovarian cancer cells via regulating Beclin‐1/PI3K/mTOR signaling pathway

Abstract: Objective: Polypeptide LTX-315 induces immunogenic cell death, thus having the potential to improve the effect of anticancer treatment. However, the function of LTX-315 in reversing chemoresistance in ovarian cancer (OC) still remains elusive.Our study aims to decipher the effect of LTX-315 on reversing the chemoresistance of OC cells and explore its mechanism. Methods: SKOV3, A2780, SKOV3/DDP, and A2780/DDP cells (cisplatin [DDP]resistant cells] were treated with different concentrations of LTX-315 (10 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…24 Beclin-1 is indispensable to initiate the autophagy process, and reduced level of autophagy in OC is consistent with decreased expression of Beclin-1. 25 Several previous studies showed that the expression of Beclin-1 was higher in ovarian epithelial cancer and borderline tumor than that in benign ovarian tumors and normal ovarian tissue, and that higher levels of Beclin-1 were inversely related to the differentiation, FIGO stage, and histological grade of OC. [26][27][28] In addition, the low expression of Beclin-1 in aggressive OC is correlated with ascending histological grade, later TNM staging, and advanced clinical stage.…”
Section: Beclin-1mentioning
confidence: 96%
See 1 more Smart Citation
“…24 Beclin-1 is indispensable to initiate the autophagy process, and reduced level of autophagy in OC is consistent with decreased expression of Beclin-1. 25 Several previous studies showed that the expression of Beclin-1 was higher in ovarian epithelial cancer and borderline tumor than that in benign ovarian tumors and normal ovarian tissue, and that higher levels of Beclin-1 were inversely related to the differentiation, FIGO stage, and histological grade of OC. [26][27][28] In addition, the low expression of Beclin-1 in aggressive OC is correlated with ascending histological grade, later TNM staging, and advanced clinical stage.…”
Section: Beclin-1mentioning
confidence: 96%
“…43 Furthermore, several anticancer agents, such as LTX-315 and tanshinone I, mediate OC cell apoptosis and the cisplatin chemosensitivity by inducing autophagy through the inactivation of the PI3K/AKT/mTOR pathway. 25,44…”
Section: Autophagy-related Signaling Pathways In Ovarian Cancermentioning
confidence: 99%